Peningkatan Kinerja Proses Melalui Analisis Bottleneck dan Prinsip-Prinsip Learn - Chalid Imran Musa (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This research explores the role of bottleneck analysis and the application of LEAN principles in improving organizational process performance. Through a literature study approach, this research identifies key concepts and the impact of bottleneck analysis and LEAN implementation on operational efficiency, adaptability and competitive advantage. The literature review was conducted by collecting relevant scientific articles, conferences, and textbooks from leading online databases, such as Scopus, Web of Science, and Google Scholar, using appropriate keywords. The literature selection process considers appropriateness of topic, quality, and year of publication, with a focus on the latest literature from 2013 to 2023. Literature content analysis and synthesis is carried out to identify main concepts, research findings, practical applications, as well as areas that require further research . It is hoped that the results of this research will provide in-depth insight into how bottleneck analysis and the application of LEAN principles can contribute to improving process performance and achieving organizational competitive advantage in a dynamic business environment